Family Story on Land-Related Tradition as Base for Land-Use Management and Sustainable Development: The Case of Indigenous Mentawai - ., Elfiondri; Pratimaratri, Uning; ., OslanAmril; Prayassita SR, Dibya (International Journal of Engineering and Technology, 2018)
Indonesian government is actively developing the indigenous villages of Mentawai. The development has brought social conflict over land and ineffective development due to the ignorance of the indigenous tradition on land. The indigenous people have a fanatically practiced tradition recorded in their family stories from which social norms on land are basically derived. Unfortunately, previous studies on the tradition in which there are rituals and taboos as the base for land-use management and development remains ignored and unexamined. The paper examines indigenous land-related tradition in village of Madobag Mentawai as basic social norms for indigenous land-use management and development. Its objectives are to identify indigenous social norms based on the tradition for possible land-use management and sustainable development. The study applies ethnography method based on theoretical approach of indigenous tradition and taboo on land. The result is that the indigenous people have a number of land-related traditions in which it is found rituals, taboos, sacred sites, and food, medical and ritual plants, plants for traditional home and canoe, and culturally important hunting area. The traditions include indigenous land-ownership, land-use for the indigenous, land-use for outsiders, and land-use for development. The traditions are social norms which should be seriously considered as base for land-use management and sustainable development. They can be as effective base for indigenous land-use management and development policy in using the land, solving social conflict over land, keeping social harmony, making policy on development, conserving environment and forest, and preserving indigenous Mentawai culture.
Keywords: Family Story; Land-Related Tradition; Land-Use Management; Social Norm.